2009
DOI: 10.1016/j.socec.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Reputational cues in repeated trust games

Abstract: a b s t r a c tThe importance of reputation in human societies is highlighted both by theoretical models and empirical studies. In this paper, we have extended the scope of previous experimental studies based on trust games by creating treatments where players can rate their opponents' behavior and know their past ratings. Our results showed that being rated by other players and letting this rating be known are factors that increase cooperation levels even when rational reputational investment motives are rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 31 publications
6
63
0
3
Order By: Relevance
“…The same situation occurred comparing treatments 3 and C3: both investments and returns C3 were slightly lower than in treatment 3, but the difference was not significant at the 5% level (see Table 2). [4] 4.4 The similarity of the corresponding treatments in Boero et al (2009) and in the current experiment was confirmed by looking at the average of B's as function of the reputation scores assigned by A. In both treatments 1 and C1, the reputation scores obtained by B players clearly depended on their returns and followed a similar logic (see Table 3).…”
Section: 3supporting
confidence: 64%
See 2 more Smart Citations
“…The same situation occurred comparing treatments 3 and C3: both investments and returns C3 were slightly lower than in treatment 3, but the difference was not significant at the 5% level (see Table 2). [4] 4.4 The similarity of the corresponding treatments in Boero et al (2009) and in the current experiment was confirmed by looking at the average of B's as function of the reputation scores assigned by A. In both treatments 1 and C1, the reputation scores obtained by B players clearly depended on their returns and followed a similar logic (see Table 3).…”
Section: 3supporting
confidence: 64%
“…Nevertheless, our experiment shows that, without incentives, a predisposition to fairness tended to guide evaluators' actions. At the same time, A players tended to trust the score expressed by third parties, just as they trusted those that emerged from the dyadic interaction in Boero et al (2009) experiment.…”
Section: 3mentioning
confidence: 95%
See 1 more Smart Citation
“… Allowing reputation formation increases trust (Berg et al 1995;Boero et al 2009;Charness et al 2011;Dubois et al 2012);  Third party punishment increases trust (Charness et al 2008);  Reduction in social distance increases trust, as shown by the effect of unbinding communication in Bracht and Feltovich (2009);  Fair procedures, such as consultative voting on the preferred outcome, increase trust in Bogliacino, Jiménez and Grimalda (2015).…”
Section: Trustmentioning
confidence: 99%
“…Sometimes unexpected opportunities for repeated exchange with previously cooperative or uncooperative partners arise 2 . Once exchange histories establish, partners with mutually beneficial non-binding agreements often reap gains from iterated trust-based trade with one another (Cochard et al, 2004;Boero et al, 2009;Kaplan et al, 2012). However, investors ceding resources (in anticipation of desired returns) remain subject to various kinds of exploitation by previously trusted partners.…”
mentioning
confidence: 99%